The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1590/0100-3984.2018.0086
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic aspects of the Achilles tendon after tenotomy for the treatment of congenital clubfoot by the Ponseti technique

Abstract: Advances in Radiology Ultrasonographic aspects of the Achilles tendon after tenotomy for the treatment of congenital clubfoot by the Ponseti technique Aspectos da ultrassonografia na avaliação do tendão do calcâneo após tenotomia para tratamento de pé torto congênito pela técnica de Ponseti

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Watzl analyzed the various phases of tendon healing by ultrasound examination in patients treated with tenotomy for congenital clubfoot; the author confirmed the ultrasound changes of the tendon structure that corresponded to those described during the biological healing process [15]. The healing mechanism after Z-plasty lenghtening was probably different, but we assumed that, in this case, the mechanical properties of the tendon were also not comparable to those of the healthy tendon.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Watzl analyzed the various phases of tendon healing by ultrasound examination in patients treated with tenotomy for congenital clubfoot; the author confirmed the ultrasound changes of the tendon structure that corresponded to those described during the biological healing process [15]. The healing mechanism after Z-plasty lenghtening was probably different, but we assumed that, in this case, the mechanical properties of the tendon were also not comparable to those of the healthy tendon.…”
Section: Discussionmentioning
confidence: 71%
“…The results of Achilles tenotomies have been extensively studied in terms of healing times. Many authors have shown complete restoration of the continuity of the tendon fibers 3-6 weeks after surgery [14][15][16][17] and good functional recovery with no restrictions in sports performance or activity [18,19]. The natural history of tendon healing after tenotomy or Z-plasty lengthening in clubfoot is not well understood [20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of Achilles tenotomies have been extensively studied, as regards healing times. Many Authors showed complete restoration of the continuity of the tendon fibers 3-6 weeks after surgery [14][15][16][17], and good functional recovery, with no restrictions in sport performance or activity [18,19]. The natural history of tendon healing after tenotomy or Z-plasty lengthening in clubfoot is not well understood [20].…”
Section: Introductionmentioning
confidence: 99%